Syntactic Relational Functions Demonstrated by Prepositional Phrases in Roro Jonggrang, Sangkuriang, and Ki Semar and Slamet Mountain - Wedhowerti; Ririt Prastika Putri; Scholastica Jessica Wendy Brilliana Putri (Universitas Tidar, 2025)
Prepositional Phrases (PPs) play a crucial role in providing detailed information about the syntactic relational functions they express in written text. This study, being qualitative in nature and employing a syntactic approach, aims at finding out the types of relational function PPs demonstrate in Roro Jonggrang, Sangkuriang, and Ki Semar and Slamet Mountain. From the analysis of the twenty data, the results yield four types of relational function (time, place, association, and direction) occurring in the three folktales. These highlight the fact that each of the relational functions detailly a clear description of the main character’s characteristics and sequential life events, and how a famous place is created. PPs prove that the three folktales are structured with distinct emphasis, where each plot and its characters, objects, and events are vividly designed and crafted.